A critical review of the intrinsic nature of vortex-induced vibrations - Sarpkaya, T. (Journal of fluids and structures, 2004)
This is a comprehensive review of the progress made during the past two decades on vortex-induced vibration (VIV) of mostly circular cylindrical structures subjected to steady uniform flow. The critical elements of the evolution of the ideas, theoretical insights, experimental methods, and numerical models are traced systematically; the strengths and weaknesses of the current state of the understanding of the complex fluid/structure interaction are discussed in some detail. Finally, some suggestions are made for further research on VIV.